Coupling the Paternò-Büchi (PB) Reaction With Mass Spectrometry to Study Unsaturated Fatty Acids in Mouse Model of Multiple Sclerosis - Chong, Leelyn; Tian, Ran; Shi, Riyi; Ouyang, Zheng; Xia, Yu (Frontiers in Chemistry, 2019)
Lipid dysregulation has been implicated in multiple sclerosis due to its involvement during and after inflammation. In this study, we have profiled fatty acids (FAs) in the mouse model of multiple sclerosis with new capabilities of assigning carbon-carbon double bond (C=C) location(s) and quantifying C=C location isomers. These new capabilities are enabled by pairing the solution phase Paternò-Büchi (PB) reaction that modifies C=C bonds in FAs, with tandem mass spectrometry (MS/MS), termed as PB-MS/MS. A series of unsaturated FAs and C=C location isomers have been identified, including FA17:1 (Δ10), FA18:1 (Δ9 and Δ11), FA18:2 (Δ9 and Δ12), and FA 20:4 (∆5, ∆8, ∆11, ∆14). Notable differences in saturated and unsaturated FAs between normal and experimental autoimmune encephalomyelitis (EAE) mice spinal cords have been detected. Furthermore, the effects of hydralazine, a scavenger of acrolein, on profile changes of FAs in mice were studied. Increased ∆11-to-∆9 isomer ratios for FA 18:1 were noted in the diseased samples as compared to the control. The present work provides a facile and robust analytical method for the quantitation of unsaturated FAs as well as identification of FA C=C location isomers, which will facilitate discovering prospective lipid markers in multiple sclerosis.